Analisis Kesalahan Gramatika dalam Presentasi Bisnis Berbahasa Inggris (Studi Kasus Mahasiswa ASMTB 2016-2017) - Hendri Pramadya (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
This research aims to identify the types of grammatical errors made by ASMTB students (2016-2017) who are studying English business presentation. This research uses descriptive method by counting the number of grammatical errors related to business deals/sales of goods and services. The results of this study show that in the oral presentation (without reading the text) several students had difficulty pronouncing English sentences based on grammatical rules. This research has successfully revealed that in a business presentation simulation, some secretarial program students make grammatical mistakes in making English sentences delivered orally in front of the class. The total number of errors found in 69 of 80 sentences. The most dominant mistake is in the use of tenses 14.49% (highest), passive sentence 13.04%, S-V agreement10.14%, double marking verb 8.69%, preposition 8.69% and the rest under six percent. Grammatical errors mostly occur due to the lackness of students in understanding English grammar because it is still influenced by the structure of the Indonesian language. Therefore, the evaluation of English grammatical errors in lecturing activities must be intensively taught in the first semester, so the students can deliver messages using effective sentences when the sentence is spoken verbally in formal situations. Keywords: Gramatical Mistakes, Business Presentation, English for Business Presentation